2022
DOI: 10.7759/cureus.25476
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium-Glucose Cotransporter-2 Inhibitors (SLGT-2i) on Cardiovascular and Renal Outcomes in Non-diabetic Patients: A Systematic Review

Abstract: Globally, cardiovascular disease (CVD) and chronic kidney disease (CKD) are the leading causes of mortality. Despite medical advances, these illnesses are still underdiagnosed and undermanaged. Sodium-glucose cotransporter-2 inhibitors (SGLT-2i) have recently emerged as a potential class of medications with promising cardiovascular and renal safety in non-diabetic patients. In this systematic review, we explored the outcomes of cardiovascular and renal protective effects utilizing SGLT-2i in three large random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(41 reference statements)
0
4
0
2
Order By: Relevance
“…When combined with ACE/ARBs inhibitors, these agents have shown a capacity to reduce cardiovascular mortality and heart failure events [ 43 , 44 ]. Additionally, they have demonstrated a potential in slowing the progression of kidney dysfunction in patients, irrespective of their diabetic status [ 45 , 46 ]. Given the limited data on SGLT2 inhibitors cost-effectiveness in CKD management and limited incorporation into standard care practices, we adopted a conservative approach in assuming that the efficacy of SGLT2 inhibitors on kidney function is comparable between patients with and without diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…When combined with ACE/ARBs inhibitors, these agents have shown a capacity to reduce cardiovascular mortality and heart failure events [ 43 , 44 ]. Additionally, they have demonstrated a potential in slowing the progression of kidney dysfunction in patients, irrespective of their diabetic status [ 45 , 46 ]. Given the limited data on SGLT2 inhibitors cost-effectiveness in CKD management and limited incorporation into standard care practices, we adopted a conservative approach in assuming that the efficacy of SGLT2 inhibitors on kidney function is comparable between patients with and without diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Una RS publicada en 2022 por Ravindran et al 148 tuvo como objetivo evaluar el beneficio de los iSGLT-2 en pacientes con ERC e insuficiencia cardiaca, en pacientes con diabetes y sin diabetes. Los autores evaluaron los efectos protectores cardiovasculares y renales con los SGLT-2i en tres grandes ECAs con una cohorte de pacientes con y sin diabetes.…”
Section: Revisión De La Literatura Y Análisisunclassified
“…Los resultados concluyen que existe una reducción significativa de las hospitalizaciones por insuficiencia cardíaca y de muerte cardiovascular y por todas las causas. Además, los iSGLT-2 impiden la progresión y la muerte por ERC 148 . Una RS publicada por Spanella et al 149 en 2020 tuvo como objetivo evaluar el impacto de sacubitrilo/valsartán en la progresión de la ERC.…”
Section: Revisión De La Literatura Y Análisisunclassified
“…The pathophysiology of the cardioprotective outcome produced by the application of SGLT-2i is not known. Possible mechanisms of action include its role in anti-inflammatory and oxidative stress pathways ( 10 ). A recent review summarized animal studies and clinical trials of SGLT-2i analogs, which showed that they have pharmacological effects in the treatment of diabetes by attenuating oxidative stress associated with T2DM, which may explain their cardiovascular benefits and have promising applications in the treatment of T2DM ( 11 ).…”
Section: Introductionmentioning
confidence: 99%